Nature of Relationships Between Atmospheric Electricity Parameters at Ground Surface and Air Ionization on the Basis of Nuclear Accidents in Power Plants and Weapons Tests - Kubicki, Marek; Mysłek-Laurikainen, Bogna; Odzimek, Anna (Frontiers in Earth Science, 2021)
In this work we present an analysis of selected atmospheric electricity parameters, measured at Geophysical Observatory in Świder (near Warsaw, Poland), in a review of the major events that resulted in the release of a significant amount of artificial radioactive substances in the Earth’s atmosphere: the radioactive accident in Fukushima, Japan, beginning 12 March 2011, followed by the 9.0 earthquake and tsunami; Chernobyl disaster (27 April 1986); and nuclear weapons testing (1958-1965). The physical mechanisms of the impact of radioactive sources on the electrical parameters of the atmosphere are analyzed. The formation of free charge (small ions, represented by electric air conductivity) and bound-induced charges (measured vertical electric field and current) by radioactive aerosol and cloud nuclei were taken into account. The values of electric field Ez, atmospheric air conductivity , and aerosol concentrations measured at a certain site depend on the time and space location of the released radioactive materials in relation to the measurement site and the meteorological situation. A frontal inflow of air masses containing radioactive substances may be noticeable at a large distance from the atmospheric electricity measuring site in fair weather conditions (Chernobyl disaster). Atmospheric precipitation plays a very important role in the transport of radioactive substances to the ground level (nuclear weapons testing). The relationship between the ionospheric potential Vi and the electric field near ground level Ez resulting from the Global Electric Circuit (GEC) concept for the presence of a strongly ionized air layer in the lower stratosphere and the ground level was disturbed in nuclear weapons testing time. The aim of this work is a qualitative characterization of discussed events. Future modeling works are needed to investigate the dependence of quantitative GEC parameters in situations of global or regional high air ionization. For this purpose, available measurements of recorded atmospheric electricity parameters will be used.